2004
DOI: 10.1108/02683940410527711
|View full text |Cite
|
Sign up to set email alerts
|

The oxymoron of control in an era of globalisation

Abstract: In response to developments around as well as within organisations, managers are faced with a control-commitment dilemma. A new rationality of governance has emerged besides the well-known rationality of bureaucratic control. This new set of governance strategies, which is presented under different labels such as commitment-based management or trust-based governance, is directed at access to and leverage of intangible resources like employee commitment, tacit knowledge and learning behaviours. In this special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
11
1
1
Order By: Relevance
“…Although this finding seems contrary to what is expected in a highly professionalized environment such as health care, several studies have found relationships between control and quality to the extent that control leads to standardized processes that ensure consistent quality in some settings (Bijisma-Frankema & Koopman, 2004). As such, this finding may have been the result of perceived consistency in patient care from a management system that strictly enforces procedures for care.…”
Section: Discussioncontrasting
confidence: 72%
“…Although this finding seems contrary to what is expected in a highly professionalized environment such as health care, several studies have found relationships between control and quality to the extent that control leads to standardized processes that ensure consistent quality in some settings (Bijisma-Frankema & Koopman, 2004). As such, this finding may have been the result of perceived consistency in patient care from a management system that strictly enforces procedures for care.…”
Section: Discussioncontrasting
confidence: 72%
“…Other streams of literature have also identified pacifying as a conflict management strategy, referring to bureaucratic control mechanisms (Bijlsma-Frankema & Koopman, 2004), distributive (Munduate & Dorado, 1998) obliging (Rahim, 2002) and forcing (Blake & Mouton, 1964) conflict management. Some scholars, however,…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…20 No. 3 forms, produce problems that are typical, unintended consequences of characteristics of the mode of governance itself (Bijlsma-Frankema and Koopman, 2004). Contrary to the vast literature on the negative aspects of formal bureaucratic control (Vroom, 1980), systematic data gathering on the negative aspects of trust-based governance has been scant until now.…”
Section: Formal Control Social Control and Trustmentioning
confidence: 99%